PENERAPAN ELECTRONIC GOVERMENT 9E-GOV) MELALUI PENYELENGGARAAN SITUS WEB PEMERINTAH PROVINSI RIAU UNTUK MEWUJUDKAN TRANSPARANSI PUBLIK - Tania Dwika Putri; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The development of information and communication technologies become a topic which widely discussed at this time especially when associated with the functions of government. The implementation of government using information and communication technologies in its development known as e-Government. It has the aim to improve the quality of public service, increas the efficiency and public transparency. As well as many other positive benefits. E-Government is a new innovation that needs to be done by government institutions. The Local Government of Riau Province in this case trying to realize the Law Decree No. 14 of 2008 concerning public disclosure through the implementation of website as a media of public information in the Riau Provincial Government. The applied media public information is www.riau.go.id as the official portal of Riau Provincial Government and this as a bridge of communication between the Local Government with public and Local Government with other Local Governments. This study used descriptive method with qualitative approach. The object of this study is the implementation of electronic government (e-gov) through the implementation website of Riau Provincial Government to achieve public transparency with the subject of 10 people. 6 people from the communications of informatics and electronics data processing department, 3 people from the user public, and 1 person from the public relations bureau secretariat of Riau Province by taking subjects using purposive sampling technique. The data collection technique in this study using in-depth observation, interview and documentation. The result of this study is public service that exist in this e-Gov has 3 classes, namely class publication, class interaction, and class transaction. Riau Provincial Government showed that the implementation of government website in class publication and class interaction have been done, while the class transaction they can not do it. In class publication, Riau Provincial Government has provided a variety if data and information in the form of news and documentations (photos and video) that can be accessed by public freely and transparently. In class interaction, it has provided facility for people to be able to participate through this website, as fas as this form of interaction that is available in the form of indirect interaction. Keyword : E-Goverment, Transparancy, Goverment